Ethical Leadership, Cooperative Conflict: Trust Development - Wiwin Fenendi; Adi Rahmat; Helwen Heri (SAINS ORGANISASI, 2023)
This study aims to determine how much influence ethical leadership, cooperative conflict, and the development of trust as mediation. This study uses a quantitative descriptive approach to measure the influence of ethical leadership, cooperative conflict, and the development of trust as mediation in the Meranti Islands Regency DPRD Secretariat. Data analysis that researchers use is a quantitative descriptive method. Meanwhile, to determine the effect of the ethical leadership, cooperative conflict, and the development of trust as mediation using the SEMPLS 6.0 application. From the results of testing the hypothesis, it can be concluded that the ethical leadership has a significant positive effect on cooperative conflict, the ethical leadership has a significant positive effect on development of trust, cooperative conflict has a significant positive effect on development of trust, and development of trust is proven to be a mediating variable between ethical leadership and i cooperative conflict. This is evidenced by a significant value (p-value) of less than 5%.